Effects of Mechanical Ventilation on Heart Geometry and Mitral Valve Leaflet Coaptation during Percutaneous Edge-to-Edge Mitral Valve Repair - Patzelt, Johannes; Zhang, Yingying; Seizer, Peter; Magunia, Harry; Henning, Andreas; Riemlova, Veronika; Patzelt, Tara A. E.; Hansen, Marc; Haap, Michael; Riessen, Reimer; Lausberg, Henning; Walker, Tobias; et al. (Jacc-Cardiovascular Interventions, 2016)
Objectives This study sought to evaluate a ventilation maneuver to facilitate percutaneous edge-to-edge mitral valve repair (PMVR) and its effects on heart geometry. Background In patients with challenging anatomy, the application of PMVR is limited, potentially resulting in insufficient reduction of mitral regurgitation (MR) or clip detachment. Under general anesthesia, however, ventilation maneuvers can be used to facilitate PMVR. Methods A total of 50 consecutive patients undergoing PMVR were included. During mechanical ventilation, different levels of positive end-expiratory pressure (PEEP) were applied, and parameters of heart geometry were assessed using transesophageal echocardiography. Results We found that increased PEEP results in elevated central venous pressure. Specifically, central venous pressure increased from 14.0 ± 6.5 mm Hg (PEEP 3 mm Hg) to 19.3 ± 5.9 mm Hg (PEEP 20 mm Hg; p < 0.001). As a consequence, the reduced pre-load resulted in reduction of the left ventricular end-systolic diameter from 43.8 ± 10.7 mm (PEEP 3 mm Hg) to 39.9 ± 11.0 mm (PEEP 20 mm Hg; p < 0.001), mitral valve annulus anterior-posterior diameter from 32.4 ± 4.3 mm (PEEP 3 mm Hg) to 30.5 ± 4.4 mm (PEEP 20 mm Hg; p < 0.001), and the medio-lateral diameter from 35.4 ± 4.2 mm to 34.1 ± 3.9 mm (p = 0.002). In parallel, we observed a significant increase in leaflet coaptation length from 3.0 ± 0.8 mm (PEEP 3 mm Hg) to 5.4 ± 1.1 mm (PEEP 20 mm Hg; p < 0.001). The increase in coaptation length was more pronounced in MR with functional or mixed genesis. Importantly, a coaptation length >4.9 mm at PEEP of 10 mm Hg resulted in a significant reduction of PMVR procedure time (152 ± 49 min to 116 ± 26 min; p = 0.05). Conclusions In this study, we describe a novel ventilation maneuver improving mitral valve coaptation length during the PMVR procedure, which facilitates clip positioning. Our observations could help to improve PMVR therapy and could make nonsurgical candidates accessible to PMVR therapy, particularly in challenging cases with functional MR.
CRIS-Team Scopus Importer:2022-11-17
Keywords: hemodynamics; mechanical ventilation; mitral valve coaptation; mitral valve regurgitation; PEEP; PMVR